MANAGEMENT OF EDUCATORS AND EDUCATION PERSONNEL BY THE PRINCIPAL OF MUHAMMADIYAH AL KAUTSAR JUNIOR HIGH SCHOOL SPECIAL PROGRAM - ANNISA, ISKA SEPTI; INAYAH, ISTIQOMAH SARAH NUR; ASTUTI, WIWIN; PEMBANGUNAN, HELDY RAMADHAN PUTRA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The teaching and educational staff management aims to organize school human resources to work according to their position and competencies to support the learning process. This research aims to provide knowledge regarding the management of teaching and educational staff carried out at Muhammadiyah Al Kautsar Junior High School Special Program in detail, discussing planning, procurement, coaching, and development of teaching and academic staff, particular strategies carried out by school principals to improve quality teaching and education staff at Muhammadiyah Al Kautsar Junior High School Special Program, termination of employment of teaching and education staff, challenges that occur when managing teaching and education staff, and evaluation of teaching and education staff. The method used in this research is a qualitative approach and literature. The type of research used is in-depth interviews. This research shows that the Muhammadiyah Al Kautsar Junior High School Special Program plans its teaching and educational staff every new school year by analyzing teaching staff based on changes in the curriculum and school programs. The contribution of this research is to increase knowledge for readers as well as evaluation material for the management of teaching and educational staff that Muhammadiyah Al Kautsar Junior High School Special Program has carried out. ABSTRAKPengelolaan tenaga pendidik dan kependidikan bertujuan untuk menata sumber daya manusia sekolah agar dapat bekerja sesuai dengan jabatan dan kompetensinya guna menunjang proses pembelajaran. Penelitian ini bertujuan untuk memberikan pengetahuan mengenai pengelolaan tenaga pengajar dan kependidikan yang dilakukan pada Program Khusus SMP Muhammadiyah Al Kautsar secara detail, membahas tentang perencanaan, pengadaan, pembinaan, dan pengembangan tenaga pengajar dan akademik, strategi khusus yang dilakukan oleh kepala sekolah. untuk meningkatkan kualitas tenaga pendidik dan kependidikan pada Program Khusus SMP Muhammadiyah Al Kautsar, pemutusan hubungan kerja tenaga pendidik dan kependidikan, tantangan yang terjadi dalam pengelolaan tenaga pendidik dan kependidikan, dan evaluasi tenaga pendidik dan kependidikan. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dan literatur. Jenis penelitian yang digunakan adalah wawancara mendalam. Penelitian ini menunjukkan bahwa Program Khusus SMP Muhammadiyah Al Kautsar merencanakan tenaga pengajar dan kependidikannya setiap tahun ajaran baru dengan menganalisis tenaga pengajar berdasarkan perubahan kurikulum dan program sekolah. Kontribusi penelitian ini adalah untuk menambah pengetahuan bagi pembaca serta sebagai bahan evaluasi pengelolaan tenaga pengajar dan kependidikan yang telah dilaksanakan Program Khusus SMP Muhammadiyah Al Kautsar.